PERJALANAN STUDI BAHASA INDONESIA DI KOREA: DAHULU, SEKARANG, DAN MENDATANG - Yang Seung Yoon (Humaniora, 2007)
The relationship between Korea and Indonesia has been staggeringly improving for the last four decades. This remarkable improvement is visible in the fields of economy, politics, as well as in social and cultural ones. For a divided country like Korea, Indonesia is considered to have an influential impact in international politics. This leads to an understanding that the need for Indonesian studies in Korea is an important factor in determining the two countries’ relationship. The Department of Malay – Indonesian Studies at Hankuk University of Foreign Studies (HUFS) was even established ten years before the establishment of the two countries’ official diplomatic ties. Since its establishment, it had experienced numerous obstacles along the way. Nevertheless, this department has flourished as the two countries continue their cooperation. Since then, Indonesian language and Indonesian area studies have become more and more well recognized and increasingly accepted in various fields in Korea. Apart from HUFS, there are also other universities in Korea offering Indonesian studies-related subjects. Still, there have been some setbacks and difficulties in securing Indonesian studies to be more beneficial to enhance the governmental relationship between the two nations. For that reason, this short paper will outline an overview on the historical background of Indonesian language and Indonesian area studies in Korea together with the impacts derived from such learning. In addition, this paper is hoped to present an increasingly ongoing relationship between Korea and Indonesia through its language and area studies in order to bring about more prosperous cooperation between the two countries in the future.